Cosmological Inflation and the N-formalism - Fransson, Emil L.A. (My University, 2011)
In this thesis we perform a study of cosmological inflation in the N-formalism. Inflation is a period of time when the physical distances in the universe grew immensely. Most theories of inflation use one or more scalar fields to drive inflation. Through fluctuations in these fields one can get theoretical predictions of the anisotropies in the Cosmic Microwave Background radiation by using the so called N-formalism.
Keywords: Fysik; Physical Sciences